(untitled) - Kevin Reichard (New York, 1994)
E-mail & Networking; E-mail for the unitialted; <Unix> mail tools; tips; UUCP; The Usenet; Using Uux, Cu, and other communications commands; communicating with other network users; The internet; For more information...
Keywords: computer networks,operating systems,unix ( computer file )